Size effect on the growth and pulverization behavior of Si nanodomains in SiO anode - Wang, Junyang; Wang, Xuelong; Liu, Bonan; Lu, Hao; Chu, Geng; Liu, Jue; Guo, Yu-Guo; Yu, Xiqian; Luo, Fei; Ren, Yang; Chen, Liquan; Li, Hong (Nano energy, 2020)
Silicon monoxide (SiO) as a promising silicon-based anode electrode of lithium-ion batteries (LIBs) has been the subject of many recent investigations. However, the complex microstructural features of SiO hinder attempts to link the microstructure changes in SiO with its electrochemical performances upon electrochemical cycling. This study employs X-ray pair distribution function (PDF), with a high-resolution transmission electron microscope (HRTEM), to investigate the microstructure of Si nanodomains in SiO and its structural evolution over the electrochemical cycling process. The experiment results reveal the size evolution of Si nanodomains in SiO during the electrochemical cycling and find it highly dependent on the initial Si domain size in SiO. If the initial Si domain size is too large, the average size of Si nanodomains would increase at first and then decrease after a certain number of cycles, which indicates the pulverization of Si domains after the electrochemical-driven growth of Si nanodomains reaches a critical point. These results suggest that an optimal initial Si nanodomain size of 4–6 nm for SiO anode materials is essential to retard the growth and subsequent pulverization process of Si nanodomains and thus to improve the cyclability of SiO during long-term cycling. [Display omitted] •Pair distribution function is employed to investigate the microstructure of SiO.•Size evolution of Si nanodomains is highly dependent on its initial domain size.•Size growth and subsequent pulverization process of Si domains in SiO are detected.•An optimal initial Si domain size of 4–6 nm for SiO anodes is proposed.